The World in Turmoil: Multilateralism in Crisis - Bhattarai, Dinesh (NCWA Annual Journal, 2025)
The United Nations was established on 24 October 1945 in the aftermath of the Second World War (WWII) with 51 founding members. Its purpose was “to save the succeeding generations from the scourge of war, promote social progress and better standards of life in larger freedom.” At its core was the principle of the sovereign equality of all member states, ensuring that no nation, no matter how powerful, had the “license” to act solely in its interests. However, the Cold War developed soon after 1945, dividing the world into a bipolar order led by the United States and the Soviet Union. The establishment of the Bretton Woods financial institutions after WWII was to ensure a “high degree of economic collaboration among the leading nations” so that the world did not relapse into economic warfare as witnessed in the preceding decades. The Western-dominated world, which created the so-called rules-based international order-including the UN as the avatar of internationalism is in disarray, with conditions worsening and becoming increasingly chaotic. Great power rivalry, deepening integration, technological interdependence, unprecedented interconnectedness and fierce competition dominate the agenda between and among nations. The outbreak of the Covid-19 pandemic accelerated the pre-existing geopolitical trends of terrorism, jihadism, cybersecurity, cryptocurrency and climate crises. Put together, these events are bedeviling nations from within and beyond, reshaping the geopolitical landscape, and raising critical questions about the sustainability of the US led liberal international order and the UN system itself. As the old order faces mounting challenges, a new global order is struggling to be born, it cannot be said with certainty whether this birth will be peaceful or descend into violence. No nation can confront today’s complex challenges and build a safer world alone. This write-up attempts to examine the current state of multilateralism, discuss implications of weakening multilateralism and finally look into the potential role of emerging nations and middle powers in building an architecture of new multilateralism. It also focuses on how Nepal can work to protect its national interests and preserve its national space and honor within an evolving geopolitical landscape.